Amerika - Kafka, Franza; Abdalrhman, Ahmed ([Cairo] master publishing, 2025)
The nivel follows karl rossmann, a young European who is sent to America after an embarrassing scandal. upon his arrival, Karl's journey unfolds as a series of bizarre, dreamlike encounters, from his interactions with eccentric relatives and strangers to his navigation of an unfamiliar
Keywords: English fiction